(untitled) (Applied Biological Research, 2016)
An experiment was conducted during 2014 and 2015 at the Department of Seed Science and Technology, College of Agriculture, Rajendranagar, Hyderabad (India) to find out variability in sixteen seed storability characteristics of 24 Pongamia pinnata genotypes. All the traits showed comparatively higher phenotypic variance than genotypic variance. All the traits, except seedling length before storage which showed moderate coefficient of variability, depicted high coefficients of variability at genotypic and phenotypic levels, heritability and genetic advance. Among the traits, speed of germination, seedling vigour index-I, seedling vigour index-II and seed germination after storage reported comparatively higher genetic estimates. Among the genotypes of TOIL-5 (Tree Oils India Limited) gave maximum mean performance for five traits i.e. initial seed germination (100%), seedling dry weight (g) before storage (4.20) and after storage (3.45), seedling vigour index-I before storage (420) and after storage (266). TOIL-12 recorded higher values for seed germination after storage (85%) and seedling vigour index-I after storage (2896) followed by TOIL 21 with high initial seedling length (64.46 cm) and initial seedling vigour index-I (6140) and TOIL 4 with high speed of germination (42.39). These genotypes were superior on the basis of above traits, hence seeds of these TOILs may be considered for further tree improvement programme by selection for the enhanced seed storability for taking up of massive afforestation programme and for green energy biodiesel production.